Room reservation and monitoring system: a smart web-based tracking system/ Nur Shaliza Sapial, Mazlam Che Yusoff Gemeti, Noorfadzilah Arifin and Khadijah Abdul Rahman - Sapial, Nur Shaliza; Che Yusoff Gemeti, Mazlam; Arifin, Noorfadzilah; Abdul Rahman, Khadijah (Faculty of Information Management, Universiti Teknologi MARA, 2012)
This paper presents the development of an online multipurpose timetable system that would be beneficial for all the staffs and students related to Universiti Teknologi Mara Cawangan Kelantan (UiTMCK). The system is designed to replace a paper-based process that gradually become unmanageable due to the increasing large volume of data. Features of the new system include online recording of forms, database query functions, electronic authorization, update, manage and monitor the progress data. We also describe the project methodology. The system is implemented on Windows platform using open-source software such as PHP4, MySQL, and Apache. Performance of the developed system is assessed practically and an efficient, and user friendly operation is demonstrated.